A novel covalent approach to bio-conjugate silver coated single walled carbon nanotubes with antimicrobial peptide. Issue 1 (December 2016) - Chaudhari, Atul; Ashmore, D'andrea; Nath, Subrata; Kate, Kunal; Dennis, Vida; Singh, Shree; Owen, Don; Palazzo, Chris; Arnold, Robert; Miller, Michael; Pillai, Shreekumar
Abstract Background Due to increasing antibiotic resistance, the use of silver coated single walled carbon nanotubes (SWCNTs-Ag) and antimicrobial peptides (APs) is becoming popular due to their antimicrobial properties against a wide range of pathogens. However, stability against various conditions and toxicity in human cells are some of the major drawbacks of APs and SWCNTs-Ag, respectively. Therefore, we hypothesized that APs-functionalized SWCNTs-Ag could act synergistically. Various covalent functionalization protocols described previously involve harsh treatment of carbon nanotubes for carboxylation (first step in covalent functionalization) and the non-covalently functionalized SWCNTs are not satisfactory. Methods The present study is the first report wherein SWCNTs-Ag were first carboxylated using Tri sodium citrate (TSC) at 37 °C and then subsequently functionalized covalently with an effective antimicrobial peptide from Therapeutic Inc., TP359 (FSWCNTs-Ag). SWCNTs-Ag were also non covalently functionalized with TP359 by simple mixing (SWCNTs-Ag-M) and both, the FSWCNTs-Ag (covalent) and SWCNTs-Ag-M (non-covalent), were characterized by Fourier transform infrared spectroscopy (FT-IR), Ultraviolet visualization (UV–VIS) and transmission electron microscopy (TEM). Further the antibacterial activity of both and TP359 were investigated against two gram positive (Staphylococcus aureus andStreptococcus pyogenes ) and two gram negative (Salmonella enterica serovar Typhimurium andEscherichia coli ) pathogens and the cellular toxicity of TP359 and FSWCNTs-Ag was compared with plain SWCNTs-Ag using murine macrophages and lung carcinoma cells. Results FT-IR analysis revealed that treatment with TSC successfully resulted in carboxylation of SWCNTs-Ag and the peptide was indeed attached to the SWCNTs-Ag evidenced by TEM images. More importantly, the present study results further showed that the minimum inhibitory concentration (MIC) of FSWCNTs-Ag were much lower ( 7.8–3.9 µg/ml with IC50: 4–5 µg/ml) compared to SWCNTs-Ag-M and plain SWCNTs-Ag (both 62.6 µg/ml, IC50: 31–35 µg/ml), suggesting that the covalent conjugation of TP359 with SWCNTs-Ag was very effective on their counterparts. Additionally, FSWCNTs-Ag are non-toxic to the eukaryotic cells at their MIC concentrations (5–2.5 µg/ml) compared to SWCNTs-Ag (62.5 µg/ml). Conclusion In conclusion, we demonstrated that covalent functionalization of SWCNTs-Ag and TP359 exhibited an additive antibacterial activity. This study described a novel approach to prepare SWCNT-Ag bio-conjugates without loss of antimicrobial activity and reduced toxicity, and this strategy will aid in the development of novel and biologically important nanomaterials.